Pengembangan Media Video Animasi Berbasis Sparkol Videoscribe Pada Pembelajaran IPS Di SD - Lasmaida Siregar, Sukmawarti (CV. PUSDIKRA MITRA JAYA, 2022)
Based on research data at SD Negeri 066668 Medan Johor found problems in the form of the learning process still on going classically, namely the use of lecture discussion methods, group work and question and answer so that in tends to be boring and less motivating for students in learning. Learning materials. Many students do not like to write and do not like to read long, convoluted sentences, so that when in class students only write modestly but they do not study it at home. The formulation of the research problem is how to develop videoscribe based animation video media in social studies learning material on ethnic and cultural diversity for class IV SD Negeri 066668 Medan Johor. This study aims to studies learning maten Ethnic and cultural diversity class IV SD Negeri 066668 Medan Johor this type of research is Research and Development (R&D) with the Borg & Gall model which was adapted by Sugiyono using 5 steps, namely: (1) potential and problems, (2) data collection; (3) product design, (4) design validation, (5) design revision. The data collection techniques used are questionnaire validation, teacher validation. Materian experts and media experts. Data analysis techniques use product data analysis in the form of media feasibility analysis and teacher response analysis. In social studies learning material on cultural diversity in Indonesia. Suggestions for further research can apply the development of animated video learning media assisted by Sparkol videoscribe in other subjects by improving the appearance of the design to make if more effective and efficient.